التربية والتعليم في علم العمران البشري عند ابن خلدون - زين, عبد الله (University of Eloued جامعة الوادي, 2022)
جرت العادة أن يرتبط الحديث عن ابن خلدون بالتاريخ والفكر التاريخي وفلسفة التاريخ- خاصة وأنه قام بثورة كوبرنيكية في حقل الكتابة التاريخية في عصره؛ لكن سوف يقع التركيز في هذا المقال على موضوع مغاير- مع أنه جزء لا يتجزأ من مسائل وقضايا العمران البشري- ألا وهو موضوع التربية والتعليم، ويرجع اهتمام ابن خلدون بهذا الموضوع لأهميته القصوى في تقدّم ورقي وتحضّر الأمم والمجتمعات؛ حتى أنه ربط التعليم بالعمران الحضري أكثر منه بالعمران البدوي؛ مما يدل على وجود ارتباط متين بين التربية والتعليم من جهة والتحضّر من جهة أخرى . استهللت هذا المقال بالتعريف بابن خلدون وذكر أبرز مؤلفاته، ومنها " مقدمة العبر " التي تناول في بعض فصولها وأبوابها موضوع التربية والتعليم، معرّفا بهما وبمنهجهما خاصة التعليم، بغرض إصلاح المنهج التربوي والتعليمي السائد في عصره، والذي انتقده بسبب النقائص والعيوب التي تضمّنها . كما تناولت علم العمران البشري في " المقدمة " وأبرزت مسائل هذا العلم ومنها التربية والتعليم، ثم تناولت علاقتهما بعلم العمران البشري، وحاولت تحديد معنيي التربية والتعليم لغة واصطلاحا، كما حاولت توضيح معنييهما في نظر ابن خلدون، ثم ختمت المقال بالمنهج التربوي والتعليمي عند ابن خلدون؛ وذلك باستعراض مبادئ وقوانين التربية والتعليم حسب وجهة نظر ابن خلدون . Abstract: It used to be that the talk about Ibn Khaldun was associated with history, historical thought and the philosophy of history - especially since he made a Copernican revolution in the field of historical writing in his time; But the focus in this article will be on a different topic - although it is an integral part of the issues and issues of human urbanization - which is the topic of education. Ibn Khaldun's interest in this topic is due to its paramount importance in the progress and advancement of nations and societies; He even linked education to urban development rather than to Bedouin urbanism. This indicates the existence of a strong link between education and education on the one hand and urbanization on the other. I started this article by introducing Ibn Khaldun and mentioning his most prominent works, including “Introduction to Lessons” Which dealt in some of its chapters and chapters the subject of education, defining them and their curriculum, especially education, with the aim of reforming the educational curriculum prevailing in his time, which he is criticized because of the shortcomings and defects that it included. It also dealt with the science of human urbanism in the "Introduction" and highlighted the issues of this science, including education, and then dealt with their relationship with the science of human urbanization, and tried to define the meanings of education and education language and terminology, and also tried to clarify their meaning in the view of Ibn Khaldun, then concluded the article with the educational and educational approach of Ibn Khaldun. ; By reviewing the principles and laws of education according to Ibn Khaldun's point of view key words : Ibn Khaldun, Introduction, Human Urbanism, Education, and Educational Curriculum.